Physical demands in elite team handball: comparisons between male and female players - Michalsik, L. B.; Aagaard, P. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The aim of the present study was to examine potential differences in the physical demands imposed on male vs. female adult elite team handball players during match-play.